Images of a Grandmother in the Movie “The Way Home” - Inero Valbuena Ancho; Aljon Delmo Galang (IAIN MADURA, 2020)
Images, as portrayed in movies, create a deep connection to its viewers, regardless of culture, history, or social status. A movie may make or break one's idea of a personality depending on role portrayal and projection. This study showcases how Filipino viewers perceive a grandmother in the movie